Supplementation of black soldier fly (Hermetia illucens) on productivity and blood hematology - Andri Cahya Irawan; Dewi Apri Astuti; I Wayan Teguh Wibawan; Widya Hermana (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
Black Soldier Fly larvae are natural antibiotics. The use of methanol extract in BSF larvae has a dual function, namely high protein content and high antibiotic content to kill Gram-negative bacteria. The biological structure of BSF larvae with antimicrobial peptide (AMP) acts as an inhibitor of pathogenic microorganisms, has a high lauric acid function as a natural antimicrobial and chitin, the polysaccharide plays a role in enhancing the immune response of the animal. This study aims to gain the best type of BSF protein from feed treatments containing live BSF, dry BSF, and BSF extract to increase blood productivity and hematology. The results of this study show that the best P3 treatment for the productivity of laying hens at the age of 18 to 26 weeks with the use of BSF extract since it contains the highest protein compared to other treatments. Productivity variables show the best P3 treatment, each egg weight 57.17 g bird-1, daily egg production 90.88%, egg mass 2408.16 g bird-1 and ration conversion 2.0. The mean hematology of the blood showed the highest P3 treatment, each erythrocyte 2.91±0.13 x 106 mm-3, leucocytes 17.69±3.68 x 103 mm-3, hematocrit 27.8±1.14%, hemoglobin 9.96±1.12%, MCV 95.77±4.41 fl, MCHC 35.99±5.21%, MCH 34.38±4.53 pg, lymphocytes 61.2 ± 4.86%, heterophile 31.2±2%, monocytes 5±0.62% and ratio H/L 0.51±0.04.